(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: Tuberculosis remains one of the major public health problems in Nepal and increasing trend of multi drug resistant and extensively drug resistant tuberculosis (MDR /XDR TB) is a big challenge. Rapid diagnosis and appropriate treatment of MDR/XDR TB is crucial. Identification and comparison of MDR TB using rapid molecular techniques (for rpob, gyrA, rrs and embB gene mutations) with reference to drug susceptibility test (DST) were the main objectives of this study. Methodology: A cross sectional study was carried out in National TB Centre (NTC). Gene Xpert, proportion method and Line Probe Assay (LPA) were used for first and second line drugs susceptibility testing (FLD-DST and SLD-DST). A total of 29 mucopurulent sputum samples were freshly collected from retreatment TB patients (Female 41.4%, Male 58.6%) with median age of 40 years attending to the four MDR TB treatment centres of eastern and central Nepal (via private courier and directly to National TB Reference Laboratory (NRL) at NTC from April 2013 to October 2017. Results: Among 29 sputum samples (Female 41.4%; all smear+ve, Male 58.6%; 16 smear+ve and 1 smear-ve), Gene Xpert MTB/RIF assay detected 100% M. tuberculosis and rifampicin resistance (rpoB gene resistant) of which, 100% were culture positive by conventional Lowenstein–Jensen (LJ) method. FLDDST was performed on all culture positives of which, 96.6% showed MDR TB and 3.4% showed mono resistance to isonizid only. SLD-DST on 29 MDRTB strains by LPA showed 100%, 58.6%, 44.8% wild type for rrs, gyrA and emb B genes respectively. Mutation for gyrA and emb B genes was 41.4% and 51.2% respectively, rrs genes none. Twelve (Female 6, Male 6) MDR TB strains were identified as pre-XDR-TB. Chi square (χ2) for trend was used to analyze Gene Xpert, smear, FLD-DST and LPA results. Conclusion: From this study, 29(100%) MDRTB were detected from retreatment TB cases by Gene Xpert and FLDDST. Almost 41.4% MDR TB strains were detected as pre-XDR TB by LPA, which were found to be higher in 15-60 years group of females and males. Samples from retreatment TB patients need to be tested by rapid molecular techniques with reference to culture and DST. SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, Vol. 14, No. 2, 2017, Page: 39-50